Pemikiran Sasterawan Negara Usman Awang - Anwar Ridhwan (Siri kajian pemikiran Sasterawan Negara, 2015)
Sasterawan Negara Usman Awang's book is a collection of papers presented in the "Seminar Pemikiran Sasterawan Negara Usman Awang" in 2006. The seminar, which carries the theme of "Building a National Literary Civilization", gives space to local literary scholars and intellectuals to analyze and analyze Usman's works. Awang from various angles. Among them, the discussion of his works with the application of theory, the discussion of Usman Awang's idealism in the production of his works, and the discussion of Usman Awang in his personality as an author, editor and friend.